Analysis Of Implementation Of Work Safety And Health Management System In Accident Field In Jabodetabek Toll Road In PT. Jasa Marga (Persero) Tbk Using Hazard And Operability Method - Harfi, Razul; Firdausi, Muhammad; Apianto, Nino (International Journal of Advanced Multidisciplinary, 2023)
PT Jasa Marga (Persero) Tbk is a company engaged in toll road management and toll road development. The method used in this study implements the Hazard and Operability method in analyzing the Occupational Safety and Health Management System with this method which can later determine the risk and level / level of the Application of Safety and Health Management Systems to accidents. And get proposed improvements to reduce existing risks. The achievement of SMK3 at PT Jasa Marga (Persero) Tbk was 74.89% in YELLOW category. This value is obtained from an average of 5 (Variables), namely K3 Commitment and Policy (76.15%), K3 Planning (72.77%), K3 Plan Implementation (75.07%), K3 Performance Evaluation and Evaluation (74 , 64%), and Review and Improvement of SMK3 Performance (75.79%). Achievement of Occupational Health and Safety Management System (SMK3) on accidents occupies level 3, namely caution. Proposed improvements to reduce the risk of potential hazards arising is to make special crossings for workers, make drainage channels in special crossing lines for workers, and require every worker to use personal protective equipment.